Islamic Boarding School Media as a Bridge of Communication for Multicultural Communities - Masuwd, Mowafg Abrahem; Ahmad Wasil; M. Hidayatulloh (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This research aims to identify and analyze the strategies of Pesantren Ngalah in responding to the dynamics of the digital era through the use of Ngalah Media as a means of communication and building trust in a multicultural society. A qualitative research approach was employed using a phenomenological method, with data collected through documentation and in-depth interviews. Data analysis was conducted using Stephen Covey's The Speed of Trust framework, which evaluates five dimensions of trust: self-trust, relationship trust, organizational trust, market trust, and societal trust. The findings reveal that Pesantren Ngalah has implemented strategic initiatives that integrate traditional pesantren values with digital advancements responsively and adaptively. Ngalah Media is vital in fostering public trust by demonstrating institutional integrity, credibility, and capability in managing digital communication. Despite these strengths, certain areas still require improvement to ensure continued relevance and positive contribution within the rapidly evolving digital communication landscape.